Best Answer

Right now, there is no solution. The sum of 2n and 12 will vary according to the value of n.

If 2n + 12 = 0, then n = -6

Q: What is the solution to (2n plus 12)?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

12+4n = 2n12+4n-4n = 2n-4n12 = -2n-1/2(12 = -2n)-6 = n

6m + m + m + 4y + n + y + 12 + 2n Group like terms: 6m + m + m + 2n + n + 4y + y + 12 Add: 8m + 3n + 5y + 12

If the question is, "What is the solution to 2n2 + 6n - 108 = 0 ?"The equation can be factored : 2n2 + 6n - 108 = (2n - 12)(n + 9) = 0If 2n -12 = 0 then n = 6If n + 9 = 0 then n = -9The roots of this equation are n = 6 and n = -9.

No. 3a 12 plus a 6 is not a solution Of an equation.

You can't. 17 + 2n = 21 + 2n gives: 2n = 4 + 2n which gives 0=4 which is not possible so the sum is not solveable.

Related questions

12+4n = 2n12+4n-4n = 2n-4n12 = -2n-1/2(12 = -2n)-6 = n

6m + m + m + 4y + n + y + 12 + 2n Group like terms: 6m + m + m + 2n + n + 4y + y + 12 Add: 8m + 3n + 5y + 12

2n plus 7 equals 19 2n equals 12 n equals 6

2(2n + 5) = 12 2n + 5 = 6 2n = 1 n = 1/2

6n -3=2n+9 6n-2n=9+3 4n=12 n=12/4 n=3

2n + 4m - 2n + m = 5m

If the question is, "What is the solution to 2n2 + 6n - 108 = 0 ?"The equation can be factored : 2n2 + 6n - 108 = (2n - 12)(n + 9) = 0If 2n -12 = 0 then n = 6If n + 9 = 0 then n = -9The roots of this equation are n = 6 and n = -9.

2n plus 4 = 2n + 4

5n + 12 = 3n Try to get all expressions with n on the left side 5n + 12 - 3n = 3n - 3n 2n + 12 = 0 Try to get rid of 12 on the left side 2n + 12 - 12 = -12 2n = -12 n = -12/2 = -6

If you mean: (2n-14)(3n+9) = 0 then it is a quadratic equation whose solution is n = -3 or n = 7

No. 3a 12 plus a 6 is not a solution Of an equation.

4n